A model based integration framework for computer numerical control system development - Li, Di; Li, Fang; Huang, Xin; Lai, Yizong; Zheng, Shixiong (Robotics and computer-integrated manufacturing, 2010)
As a typical complex embedded computer control system, Computer Numerical Control (CNC) system development is confronted with a great challenge because of its specific requirements as well as some recent development trends such as ever more complex products while at lower prices and shorter develop cycle. In this paper, a model based integration framework (CNCMIF) for CNC system design and development is presented, which integrates modeling, simulation, verification and implementation in a uniform environment. The CNCML (CNC modeling language) with well defined syntax and unambiguous semantics is developed to describe the CNC system in an accurate and explicit way. Model transformation strategy for formal verification and code automatic generation for implementation in the framework are also presented. The approach is an attempt to create an infrastructure to support the CNC system design in an efficient way, while at the same time guarantees the function and performance requirements with advanced capability of the system such as modularity, flexibility, reusability, etc.